Numerical Methods for Fluid Dynamics - Durran, Dale R. (Springer, 2012)
This scholarly text provides an introduction to the numerical methods used to model partial differential equations, with focus on atmospheric and oceanic flows. The book covers both the essentials of building a numerical model and the more sophisticated techniques that are now available.